ISSUES OF SOLVING THE PROBLEM OF THE DEVELOPMENT OF EDUCATIONAL AND COGNITIVE ACTIVITY OF STUDENTS IN THE FIELD OF PHYSICAL CULTURE - Suvonov Kadyr Yoldoshevich (American Journals Publishing, 2023)
The article discusses methods and systems for solving problems of the development of physical culture and physical education of students.
Keywords: physical and mental development, educational and cognitive activity, physical education, physical exercises.